IMF Research Bulletin, December 2007. (IMF Research Bulletin; IMF Research Bulletin ;, 2007)
IMF research summaries on governance of banks (by Luc Laeven) and on whether there is a foreign aid paradox (by Thierry Tressel); country study on Mozambique (by Jean A.P. Clement and Shanaka J. Peiris); listing of visiting scholars at the IMF during July 2007-January 2008; listing of contents of Vol. 54, Issue No. 4 of IMF Staff Papers; listing of recent IMF Working Papers; listing of recent external publications by IMF staff; and a call for papers for the upcoming Conference on International Finance.